กายวิภาคศาสตร์ใบและลำต้นของพืชเบียนวงศ์กาฝาก (Loranthaceae) ในจังหวัดอุบลราชธานี - Kesonbua, Wiroj; Suriyon, Puttisan; Lakhunthod, Preyanuch (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2025)
Leaf and Stem Anatomy of Parasitic Plants within the Loranthaceae Family at Ubon Ratchathani Province Wirot Kesonbua, Puttisan Suriyon and Preyanuch Lakhunthod รับบทความ: 7 ตุลาคม 2567; แก้ไขบทความ: 20 มกราคม 2568; ยอมรับตีพิมพ์: 25 มกราคม 2568; ตีพิมพ์ออนไลน์: 4 มิถุนายน 2568 บทคัดย่อ จากการศึกษาลักษณะกายวิภาคศาสตร์ใบและลำต้นของพืชเบียนวงศ์กาฝากบริเวณพื้นที่ป่า เต็งรังในจังหวัดอุบลราชธานี จำนวน 4 ชนิด ได้แก่ Dendrophthoe pentandra (L.) Miq. Helixanthera parasitica Lour. Macrosolen cochinchinensis (Lour.) Tiegh. และ Scurrula atropurpurea (Blume) Danser โดยวิธีการลอกผิวใบและตัดตามขวางด้วยใบมีดโกนและกรรมวิธีพาราฟิน พบลักษณะทั่วไปของพืชที่ศึกษาคือ เซลล์ในเนื้อเยื่อชั้นผิวใบทั้งสองด้านมีรูปร่างหลายเหลี่ยมหรือรูปร่างไม่แน่นอน ผนังเซลล์เรียบหรือเว้า ปากใบเป็นแบบพาราไซติก พบในเนื้อเยื่อชั้นผิวใบทั้งสองด้าน อยู่ระดับเดียวกับเนื้อเยื่อชั้นผิว บางชนิดมีสารสะสมเป็นเซลล์เม็ดน้ำมันและบางชนิดมีไทรโคมเป็นปุ่มเล็ก ชั้นมีโซฟิลล์ประกอบด้วยเซลล์ที่มีรูปแบบเดียว หรือสองแบบที่มีใบสองหน้าเหมือนกันและใบสองหน้าต่างกัน มัดท่อลำเลียงบริเวณเส้นกลางใบมี 3–6 มัด เนื้อเยื่อชั้นผิวของก้านใบไม่มีไทรโคมหรือมีไทร-โคมแบบหลายเซลล์ ชั้นคอร์เทกซ์เป็นเนื้อเยื่อพาเรงคิมาที่เซลล์มีผนังบาง พบโครงสร้างสารหลั่งกระจายอยู่ทั่วไป มัดท่อลำเลียงบริเวณก้านใบมีจำนวนมัดเดียวหรือหลายมัด พบสารสะสมเป็นแบบผลึกรูปปริซึมกระจายรอบ ชั้นเพริเดิร์มของลำต้นมีเลนติเซลกระจายทั่วไป บางชนิดมีสารสะสมติดสีแดงเข้มในชั้นเฟลโลเดิร์ม โฟลเอ็มมีเซลล์เส้นใยผนังหนาล้อมรอบ วงปีไม่ชัดเจน เซลล์เวสเซลมีรูปร่างกลมหรือรี มีรูปแบบเป็นแบบเดี่ยว แบบแฝด และแบบกลุ่ม การเรียงตัวของเวสเซลเป็นแบบกระจาย พาเรงคิมาในแนวรัศมีมี 1–8 แถว พบสารสะสมแบบผลึกรูปปริซึมในเซลล์บริเวณไส้ไม้ โครงสร้างที่สามารถนำไปใช้สร้างรูปวิธานสำหรับการระบุชนิด ได้แก่ ไทรโคม ชั้นมีโซฟิลล์ และจำนวนมัดท่อลำเลียงของก้านใบ กายวิภาคศาสตร์ของพืชวงศ์กาฝากแสดงลักษณะของพืชทนแล้ง พืชน้ำ และพืชที่ชื้นปานกลาง เป็นการปรับตัวของพืชเบียนที่เกาะอาศัยอยู่บนพืชให้อาศัยเพื่อสามารถดำรงชีวิตในแหล่งที่อยู่อาศัยย่อยที่มีสภาพแวดล้อมเฉพาะภายในระบบนิเวศของป่าเต็งรัง คำสำคัญ: กายวิภาคศาสตร์พืช พืชเบียน วงศ์กาฝาก การปรับตัว Abstract Anatomical studies of the leaves and stems of four species of parasitic plants in the family Loranthaceae found in the deciduous forest of Ubon Ratchathani province, namely Dendrophthoe pentandra (L.) Miq., Helixanthera parasitica Lour., Macrosolen cochinchinensis (Lour.) Tiegh., and Scurrula atropurpurea (Blume) Danser, were conducted using epidermal peeling, transverse sections prepared through freehand sectioning and the paraffin process. The general characteristics of the plants studied include polygonal or irregularly shaped cells in both surface tissues. The cell walls are smooth or curved. The stomata are paracytic and found on both surfaces, with typical stomata. Some species have substances that accumulate as oil droplets, and some have papillae trichomes. The mesophyll layer consists of cells with a single pattern or two types, with unifacial or bifacial leaf. There are 3–6 vascular bundles in the leaf midrib. The epidermis of the petioles is either glabrous or covered with multicellular trichomes. The cortical layer comprises thin–walled parenchyma cells, and secretory structures are scattered throughout. There are 1 to several vascular bundles in the leaf petiole. Accumulated substances were observed in the form of prism–shaped crystals distributed around the vascular bundles. The stem periderm contains lenticels scattered throughout. In some species, dark red accumulated substances are presence in the phelloderm layer. The phloem is surrounded by thick-walled fibers. The annual rings are indistinct. The vessel cells are round or oval in shape, and there is solitary, paired, and clustered vessels. The vessel arrangement in wood is diffuse–porous wood. The radial parenchyma has 1 to 8 rows. Prismatic crystal deposits are found in the cells of the pith. Structures that can be used to construct a key for species identification include trichomes, mesophyll, and the number of vascular bundles in the petioles. The anatomy of the family exhibits characteristics of drought–tolerant plants, aquatic plants, and moderately moist plants. It represents an adaptation of parasitic plants that live on host plants, enabling them to survive in microhabitats with specific environmental conditions within deciduous forest ecosystem. Keywords: Plant anatomy, Parasitic plants, Loranthaceae, Adaptation